Impact of peer bullying on school students with and without ADHD symptoms: a cross-sectional study from Pakistan - Muhammad Saleem; Rozmi Ismail; Arena Che Kasim; Ezarina Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2015)
The present study aims to identify the impact of peer bullying on school students with and without ADHD symptoms. Sample comprised of one thousand (N=1000) school going children with an age range 9-15 years whom belong to grades 6-10, were selected by using purposive sampling technique, taken from two major cities of Southern Punjab (Multan & Bahawalpur) Pakistan. Two scales were used for data collection; Conners Teacher Rating Scale – (Revised) developed by © Conners (1997), followed by Olweus Bullying Questionnaire by © Olweus (2007). Tools were formally translated by following the guidelines of Eremenco, Cella, and Arnold (2005) into national language of Pakistan (Urdu) and employing pilot study. ANOVA, standard deviation, t-test, and mean were calculated using SPSS (21.0) to process the results. Findings suggest (t=10.096, P-Value=0.000) showing that there is significant difference between the mean scores of bullying with ADHD and without ADHD symptoms students. However, results on gender differences indicate (t=2.260, P-Value=0.024) there is a significant difference between the impact of bullying on boys and girls. Results also show (F= 7.783, P= 0.000) there is also noticeable difference in terms of bullying among all students in different grades at 5% level of significance. Limitations of the study and recommendations for future research are also enclosed.